Autonomous Migrant Mobilisations in Libya and (Counter-)Externalisation: Transnational Spatial Configurations of Solidarity - Cuttitta, Paolo (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
The restrictive, violent evolution of the Libyan migration and border regime has been strongly determined by the externalisation efforts of European policymakers. Yet self-organised initiatives of migrants in Libya, and the more-than-local solidarity spaces they establish, generate counter-externalisation dynamics aimed at transforming such a regime and steering it in the opposite direction. To shed light on these dynamics, the paper provides an overview of self-organised forms of protest and mobilisation of people on the move in Libya in the last two decades. While these migrant initiatives result from endogenous forms of solidarity, they also inspire and trigger different forms of exogenous, pro-migrant solidarity from different categories of actors across places. Thus, solidarity follows multiple directions and creates specific solidarity spaces at different scales. Spatialities and directionalities produced by the interplay between solidarity and more-than-local migrant or pro-migrant mobilisations can be conceptualised as acts of counter-externalisation, reacting to the externalised regime of migration containment that has been established in Libya since the early 2000s. The paper first introduces the Libyan migration regime from the perspective of European border externalisation. Then, it reconstructs the history of migrant mobilisations in Libya from the Gaddafi period to the present day, including more recent developments such as the establishment of the movement “Refugees in Libya” and its international support network “Alliance with Refugees in Libya.” The concluding section analyses the spatial configurations of solidarity emerging from migrant mobilisations in Libya against the background of European border externalisation.